KLINIK KESEHATAN JIWA DI BANJARBARU - Rizky Fitria; Muhammad Deddy Huzairin (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2025)
The number of issues circulating regarding mental health problems is increasing today, and it is not uncommon for criminal acts related to a person's mental health to occur. Mental health or better known as mental health is one of the aspects of emotional health that affects the way a person thinks, feels, and acts in living their daily lives. There are problems in mental health facilities, such as lack of experts, uncomfortable facilities, and long waiting times. This makes mMental Healthental health facilities receive a lack of assessment. In overcoming mental health problems that continue to increase, promotions are carried out about the importance of mental health and also facilities that can overcome this problem. In helping to overcome existing problems, a mental health clinic was designed that focuses on curing psychiatric problems. In the design of the clinic, there is an approach method related to mental health, namely the environmental psychology method. The method used is a combination of the human psychological environment and space.